Intervención del terapista respiratorio en paciente masculino de 63 años con diagnóstico de neumonía asociada a la comunidad. - Arguello Gaibor, Shirley Lisseth (2023)
The focus of this study is the intervention of a respiratory therapist in a 63-year-old man diagnosed with community-associated bacterial pneumonia. One of the most common lung diseases affecting children and older adults worldwide is acquired bacterial pneumonia. The Streptococcus pneumoniae bacterium is the main responsible for this pathology. Community-acquired bacterial pneumonia has been considered a serious health problem in our country for the last 5 years, since it is one of the 3 most frequent causes of morbidity in children and the elderly, and one of the main reasons for visiting childcare centers; doctor and hospitalization in several home hospitals. The patient, a 63-year-old man, presented with type 2 diabetes mellitus, arterial hypertension, and immunosuppression, all of which are important risk factors for the development of this respiratory disease. Cigarette smoke, since the patient lives with a relative who smokes regularly, is also an important cause of community-acquired bacterial pneumonia in this case.